The Effect of Financial Performance on Stock Prices in Telecommunication Companies Listed on the IDX - Andi Awalia Ramadhani; Darman; Juliana Kadang; Suryadi Samudra (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to find out and analyze the influence of financial performance on the stock price of telecommunication companies listed on the IDX. This type of research is quantitative. The population in this study is the financial statements of telecommunication companies on the IDX which amount to 18 companies. The analysis technique used is multiple linear regression analysis. The results of this study show that financial performance variables  have a significant effect on the stock prices of telecommunication companies listed on the IDX. The current ratio partially has a significant effect on the share price of telecommunication companies listed on the IDX,  the debt to equity ratio partially has a significant effect on the share price of telecommunication companies listed on the IDX,  return on equity partially has a significant effect on the share price of telecommunication companies listed on the IDX and total asset turnover partially has a significant effect on the share price of telecommunication companies listed on the IDX